Pengaruh Metode Ceramah, Diskusi Dan Demonstrasi Dalam Meningkatkan Keterampilan Interpersonal Peserta Didik - Lediana; Nofikasyara Dhea; Fortunata Blandina Panamuan (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This Arikel aims to find out the influence of lecture methods, discussions and demonstrations in improving the interpersonal skills of students. The method used is a literature study, where the author does not need to go directly into the field in collecting data. Through this method, the author strives to collect, search and evaluate various sources of literature that are relevant to the topic discussed. From these sources, the author found that in the learning process, it turns out that it does not only use one method, but can use learning methods that can be used by teachers in providing learning to students such as the Lecture, Discussion and Demonstration method which in this method will indirectly improve the interpersonal skills of each student. The method used has a positive impact on students because it makes it easier for them to understand the learning delivered. The role of teachers is also very important in honing interpersonal skills because educators can explain or implement their interpersonal skills.